Food security adaptation analysis to climate change in Bekasi District - Iswarani, Ni Putu Diva; Ismail Masjud, Yunita (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Global climate change is a natural outcome of rising greenhouse gas concentrations in the atmosphere brought on by people's continued pursuit of activities that will meet their demands for food in order to support their lives (Wilis R., 2014). Food security is negatively impacted by climate change. Agricultural productivity will be hampered and food security disrupted by too much or too little rainfall. One of the region that indicated to have a crisis in food securtity in climate crisis. Bekasi is one of the city that located in West Java. Methods: This study tried to employ a methodical literature review approach and analysis to the data that get from the literature review approach. Finding: There are some changes in the data from the rainfall averge, and the productions of the plants commodity. Conclusion: The grown in food security that occurred was also influenced by the climate crisis that occurred in Bekasi Regency, where the average rainfall experienced increased and decreased. In the reality the development that is happening in Bekasi is also the driving force behind the crisis in the food security, because the land to grow the plant is already changing to factory and others.